Influence of chlorhexidine application on longitudinal adhesive bond strength in deciduous teeth - Vicente Castelo Branco Leitune; Fernando Freitas Portella; Priscila Veit Bohn; Fabrício Mezzomo Collares; Susana Maria Werner Samuel (Sociedade Brasileira de Pesquisa Odontológica, 2011)
The aim of this study was to evaluate the influence of applying 2% chlorhexidine for 30 seconds after phosphoric acid conditioning of dentin on the immediate and long-term bond strengths in deciduous teeth. The occlusal enamel was removed from 40 human sound deciduous molars, which were exfoliated by natural means, and the dentin was conditioned with 37% phosphoric acid for 15 seconds and washed with running water. The specimens were divided into two groups of 20 teeth. The test group received an application of 2% chlorhexidine for 30 seconds prior to a three-step etch-and-rinse adhesive system, whereas the control group received only the adhesive system. Three cylindrical restorations were made with a composite resin for each tooth. Ten teeth in each group were submitted to a microshear bond strength test after 24 hours, while the remaining teeth were stored in distilled water at 37 °C for 6 months before testing the microshear bond strength. The test group had a higher bond strength than did the control group after 6 months of storage. No statistical differences were found when groups with the same dentin treatment were compared at different times. Short applications of chlorhexidine at low concentrations prevent hybrid layer degradation and positively affect bond strength over time.